EVALUATION OF EFFICIENCY OF FINANCING TRANSPORT INFRASTRUCTURE PROJECTS REALIZED IN THE FRAMEWORK OF PUBLIC PRIVATE PARTNERSHIP - S. B. Vasiliev; E. A. Vdovina (Научный вестник МГТУ ГА, 2016)
The article examines the basic approach to evaluating efficiency of financing transport infrastructure projects realized in the framework of public private partnership. The main ways of the project realization are identified, and their main advantages and disadvantages are described. Detailed elaboration and structuring of infrastructure projects are grounded.